Placing agricultural research and technology transfer in one organization: Two experiences from Colombia - Kaimowitz, David (Wiley, 1990)
Based on two experiences from Colombia, placing agricultural research and technology transfer in the same institution is found to be neither a necessary, nor sufficient, condition for effective co‐ordination between the two activities or improved institutional performance. Additional factors to consider include: (1) the specificity of the problems addressed; (2) the institution's capacity to manage the co‐ordination; (3) status differences and competition over resources; (4) institutional size; and (5) the level of politicization of the technology transfer activities.